151 Prevalence of Coronary Artery Disease and Major Adverse Cardiovascular Events in Patients with A Zero Calcium Score: A Prospective Cardiac CT Study. (31st May 2014) - Rajani, Nikil K; Joshi, Francis R; Babar, Judith; Balan, Anu; Gopalan, Deepa; Rudd, James HF
Abstract : Introduction: Cardiac computed tomography (CT), consisting of coronary artery calcium (CAC) scoring and CT angiography (CTa), is recommended by NICE for the exclusion of coronary artery disease (CAD) in intermediate-risk symptomatic patients. Coronary calcification is pathognomonic of underlying CAD, but a zero CAC score cannot exclude CAD with certainty due to non-calcified coronary plaques. We evaluated the prevalence of CAD and the rate of major adverse cardiac events (MACE) in patients with a zero CAC score in comparison to patients with a non-zero CAC score. Methods: From November 2009 to April 2013, 458 patients with chest pain underwent CT to exclude CAD. All subjects had CAC scoring. The majority of studies included contrast-enhanced, 128-slice, dual-source CTa. Scans were dual-reported by a cardiac radiologist and a cardiologist. MACE and all-cause mortality were determined through searches of regional databases. Results: 458 symptomatic patients underwent CAC scoring. 247 patients (53.9%) had a CAC score of zero and 211 (46.1%) had non-zero CAC score, with a median score of 74 (interquartile range [IQR]: 13–223). Patients with a zero CAC score were younger (52 vs. 62 years, p < 0.0001) and more likely to be female (59.9 vs. 39.8%, p < 0.0001), but less likely to be hypertensive (26.3% vs. 44.1%, p < 0.0001), diabetic (6.9 vs. 14.7%, p = 0.0065), or have a smoking history (29.6 vs. 40.8%, p = 0.0121). Current smoking status and obesity did not differ between groups. There was a trend towards a family history being more common in those with zero CAC scores (37.2 vs. 29.9%, p = 0.09). 424 studies (92.6%) included CTa. Table 1 illustrates the breakdown of CTa findings according to CAC score. Over a median follow-up of 536 days (IQR: 316–925), 2 MACE events (0.8%) were recorded in the cohort with zero CAC (n = 247), compared to a MACE rate of 1.9% (4 events) in those with non-zero CAC scores (n = 211). Both MACE events in the zero CAC group (1 acute MI and 1 emergent revascularisation) occurred in patients with CTa results suggesting normal coronaries.A CAC of zero was associated with a 99.2% negative predictive value for MACE over the course of follow-up. When MACE and all-cause mortality were combined, a CAC score of zero was associated with significant protective effect (Hazard Ratio 0.24, 95% CI: 0.07–0.86, p = 0.028, Figure 1 ). Conclusion: Cardiac CT is an increasingly important tool for risk stratification. Reassuringly, a zero CAC score is associated with low rates of both obstructive CAD and MACE, emphasising its utility as a means to rule out CAD. Despite the presence of non-calcified CAD in some patients with a CAC of zero, these patients had a good prognosis.